MicroRNA-143-3p/TBX3 Axis Represses Malignant Cell Behaviors in Bladder Cancer. (27th January 2022) - Huang, Lifu; Zhang, Xianjun; Li, Feiping; Wang, Xiaohong
Abstract : Objective . To offer new insight for bladder cancer therapy through researching the microRNA-143-3p/TBX3 axis. Methods . Differentially expressed microRNAs in bladder cancer were provided by databases to find microRNA that may regulate TBX3. qRT-PCR was utilized to test levels of TBX3 mRNA and microRNA-143-3p. Their binding was verified with a dual-luciferase method. Malignant cell behaviors were examined by cell functional experiments. Levels of TBX3 protein and proteins pertinent to epithelial-mesenchymal transition (EMT) were tested by western blot. Results . TBX3 was highly expressed in bladder cancer cells. MicroRNA-143-3p presented the most conspicuously negative correlation with TBX3, and they had binding sites. Cell functional experiments proved that TBX3 facilitated bladder cancer cell functions and EMT. MicroRNA-143-3p was demonstrated to downregulate TBX3 expression. Rescue assay further illuminated that microRNA-143-3p repressed bladder cancer cell functions and EMT through downregulating TBX3 expression. Conclusion . These data all indicated that TBX3 was modulated by microRNA-143-3p and acted as a cancer promoter gene in bladder cancer progression via affecting tumor proliferation, migration, invasion, and EMT. Therefore, a microRNA-143-3p/TBX3 network might be an underlying target for bladder cancer.